Assessing the Role of Virtual Surgical Planning in Mandibular Reconstruction With Free Fibula Osteocutaneous Graft. Issue 6 (September 2019) - Saini, Varun; Gaba, Sunil; Sharma, Shagun; Kalra, Praveen; Sharma, Ramesh K.
Abstract : Background: The role of virtual surgical planning and three-dimensional printing in improving the accuracy, precision, functional and aesthetic outcomes have been demonstrated in the literature; however, there is a dearth of studies evaluating these parameters. Objective: This study was carried out at a tertiary care center in North India to assess the accuracy of virtual surgical planning in mandibular reconstruction. Method: All the included patients were preoperatively assessed with a contrast enhanced computed tomography (CECT) of head and neck. Based on the dimensions a patient-specific fibula cutting guide was fabricated by three-dimensional printing. All patients were evaluated with a postoperative CECT at 6 months of follow-up. The precision outcomes were measured by comparing surgical results with the images of the preoperative virtual planning based on several measurements on the reconstructed mandible such as anteroposterior measurement, transverse measurement, height of the mandible, angle of the mandible, and lateral tilt. The secondary outcomes analyzed were the mean total operative time, mean ischemia time, and morbidity parameters. Result: Twelve consecutive patients (6 male, 6 female) with mean age of 33.1 ± 11 years who underwent free fibula graft mandibular reconstruction were included in the study. The mean difference in the anteroposterior, transverse, and height dimensions were 0.87 ± 0.43 mm ( P = 0.24), 2.43 ± 3.72 mm ( P = 0.64), and 1.08 ± 0.67 ( P = 0.88), respectively. The difference in the angles of the reconstructed mandible was 2.37 ± 3.92 degrees ( P = 0.51) and of lateral tilt was 1.57 ± 1.5 degrees ( P = 0.54). The mean total operative time was 639 ± 27.2 minutes and mean ischemia time was 88.4 ± 8.6 minutes. Conclusion: All the patients had satisfactory aesthetic results and good oral function at 6 months postoperative period. Abstract : Supplemental Digital Content is available in the text